Transcranial Doppler and Near-Infrared Spectroscopy Can Evaluate the Hemodynamic Effect of Carotid Artery Occlusion - Fabrizio Vernieri; Francesco Tibuzzi; Patrizio Pasqualetti; Nicola Rosato; Francesco Passarelli; Paolo Maria Rossini; Mauro Silvestrini (2003)
Background and Purpose— Cerebral hemodynamic and metabolic changes can compensate for the decrease in cerebral blood flow occurring in patients with carotid occlusive disease. At present, a complete assessment of the cerebral adaptive status is only possible with positron-emission tomography. Near-infrared spectroscopy (NIRS) is a noninvasive technique that, providing a real time assessment of fluctuations in cerebral hemoglobin, has been used to estimate the cerebral blood volume and to measure cerebral vasomotor reactivity (VMR). Moreover, NIRS technology, by allowing the absolute measurement of absorption and scattering coefficients of brain, can determine the oxyhemoglobin and deoxyhemoglobin concentrations in situ in the blood stream. Methods— In order to evaluate different aspects of the cerebral hemodynamic status, 27 subjects with symptomatic and asymptomatic carotid artery occlusion and 30 healthy subjects underwent a simultaneous examination by means of transcranial Doppler (TCD), able to reliably detect collateral circulation and VMR, and NIRS at rest condition and during CO 2 reactivity test. Results— The main finding of this study was the demonstration of a difference between asymptomatic and symptomatic patients in terms of mean flow velocity increase (52.4% versus 21.0%; P <0.001) estimated by TCD and of hemoglobin saturation increase measured by NIRS (6.8% versus 3.8%; P =0.015). Conclusions— The opportunity to perform NIRS and TCD simultaneously provides useful information about both hemodynamic and metabolic cerebral adaptive status in patients with occlusive disease in a simple, noninvasive, and reliable way.